2020
DOI: 10.1016/j.ajog.2020.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Stillbirth is associated with increased risk of long-term maternal renal disease: a nationwide cohort study

Abstract: Background Stillbirth is a devastating adverse pregnancy outcome that may occur without any obvious reason or may occur in the context of fetal growth restriction, preeclampsia, or other obstetric complications. There is increasing evidence that women who experience stillbirths are at greater risk of long-term cardiovascular disease, but little is known about their risk of chronic kidney disease and end-stage renal disease. We conducted the largest study to date to investigate the subsequent risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 37 publications
2
19
0
1
Order By: Relevance
“…We excluded multiple pregnancies ( n = 148,339) and pregnancies with implausible dates of delivery ( n = 312) from all analyses at baseline. We also excluded women who had stillbirths ( n = 14,107) to avoid potential confounding since they are more likely to experience preeclampsia compared with women who only have live births, and they are at increased risk of long-term CKD [ 21 ] ( S1 Fig ).…”
Section: Methodsmentioning
confidence: 99%
“…We excluded multiple pregnancies ( n = 148,339) and pregnancies with implausible dates of delivery ( n = 312) from all analyses at baseline. We also excluded women who had stillbirths ( n = 14,107) to avoid potential confounding since they are more likely to experience preeclampsia compared with women who only have live births, and they are at increased risk of long-term CKD [ 21 ] ( S1 Fig ).…”
Section: Methodsmentioning
confidence: 99%
“…The tool was developed after exhaustively reviewing relevant literature [13,16,20,[23][24][25][26][27][28]. A minor modification was made to suit the local context.…”
Section: Data Collection Tool and Proceduresmentioning
confidence: 99%
“…Previous researchers have revealed that asphyxia, maternal infection, non-communicable disease, chronic illness, resident, interpregnancy interval, previous preterm birth, premature rupture of membrane, the induced onset of labor, prolonged labor (>12 hours), multiple pregnancies, mode of delivery, maternal age, place of residence, education level, parity, antenatal care utilization, place of delivery, body mass index (BMI) and anemia, previous stillbirth, uterine rupture, abruption placentae, belonging to the poorest family, antepartum hemorrhage, maternal hypertensive disorder during pregnancy, and small weight-for gestational age babies are significant predictors of stillbirth [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 19 Such adverse delivery outcomes can be associated with detrimental outcomes for the mother and the infant over the long term. 47 , 48 …”
Section: Discussionmentioning
confidence: 99%